CREATING A GLOBAL NETWORK OF ARMENIAN PSYCHOLOGISTS - Takooshian , H.; Kalayjian , A. (Արդի հոգեբանություն, 2021)
“Can we create a global network of Armenian psychologists?” This question arose in 2109 at the 100th anniversary conference at Yerevan State University. This three-part report details: (1) The challenge, (2) The current status of Armenians in psychological science and practice in the Republic, the USA, and elsewhere in the Diaspora. (3) Conclusion about the feasibility of a cross-national census of indigenous Armenians in psychology. Creation of the association of professional psychologists for the humanitarian mission "Psychology can withstand crises, disasters and wars."